2016
DOI: 10.3109/14397595.2015.1123345
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to microtubule-associated protein-2 in the cerebrospinal fluid are a useful diagnostic biomarker for neuropsychiatric systemic lupus erythematosus

Abstract: Anti-MAP-2 antibodies could be detected in the CSF of 33.3% of patients with NPSLE, and its presence was highly specific for NPSLE. We propose that CSF anti-MAP-2 antibodies are a novel and useful diagnostic biomarker for NPSLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…MAP -2 regulates the nucleation and stabilization of microtubules, organelle transport protein kinases that are involved in signal transduction 55) . In a study by Yamada et al, 33.3% of NPSLE patients tested positive for anti -MAP -2 in the CSF 54) . Williams also reported that 17% of SLE patients had anti -MAP -2 in contrast to 4% of neurologic injury/disease control patients 56) .…”
Section: Antimicrotubuleassociated Protein 2 Antibodies (Anti -Map -2)mentioning
confidence: 93%
See 1 more Smart Citation
“…MAP -2 regulates the nucleation and stabilization of microtubules, organelle transport protein kinases that are involved in signal transduction 55) . In a study by Yamada et al, 33.3% of NPSLE patients tested positive for anti -MAP -2 in the CSF 54) . Williams also reported that 17% of SLE patients had anti -MAP -2 in contrast to 4% of neurologic injury/disease control patients 56) .…”
Section: Antimicrotubuleassociated Protein 2 Antibodies (Anti -Map -2)mentioning
confidence: 93%
“…MAP -2 is one of the abundant groups of cytoskeletal components predominantly expressed in neurons 54) . MAP -2 regulates the nucleation and stabilization of microtubules, organelle transport protein kinases that are involved in signal transduction 55) .…”
Section: Antimicrotubuleassociated Protein 2 Antibodies (Anti -Map -2)mentioning
confidence: 99%
“…reported that CSF anti-ribosomal P titer was significantly higher in NPSLE patients with anti-microtubule-associated protein-2 (MAP-2) Ab than in those without MAP-2 Ab or non-NSPLE patients. 32 They did not, however, examine the combined effect of both auto Abs. We also measured anti-ribosomal P Ab in CSF; however, the anti-ribosomal P positivity was low (8.2%) for a relevant statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher anti-microtubule-associated protein-2 (anti-MAP-2) antibody titers were discovered in the CSF of patients with NPSLE compared to the CSF of non-NPSLE controls. Anti-MAP-2 antibody prevalence was 33.3% in NPSLE ( 146 ).…”
Section: Disease Markers For Neuropsychiatric Sle (Npsle) and Sle With Other Comorbiditiesmentioning
confidence: 98%